Acurácia dos métodos para estimativa do volume comercial de clones de Eucalyptus sp - Thiersch, Cláudio Roberto (2006)
This study aimed at evaluating the precision and the accuracy of the following methods: Two diameters, geometric method, single entry equation, double entry equation associated or not with ipsometric relation in the estimation of volume, for defining a precise and low cost strategy for trials both for individual trees and for forestry inventory parcels. Data base used encompassed 36 parcels of 400 m2 . Around the parcels, 216 trees were sealed. Two clones (hybrid of E. grandis and E. urophylla), at the ages of 3; 4, 5 and 6 years, belonging to three different sites of a farm owned by Aracruz Celulose S. A., in East Brazil. The single entry method and the method of the two diameters should not be used for determining volume, if high precision is sought. The double entry method, with real total height, was precise in evaluating volume; however it was not exact enough in all site index situations. The geometric method was precise and exact for the two clones for all ages and site index studied, when the diameters were measured at 0.1m, 1.3m of height and the angular coefficients were estimated, however it was not exact enough for all situations studied. The diameters mensuration at 0.1m, 1.3m and (ht-2)/2 of height, of a single tree in each diametric class, for each site-age interaction, was sufficient for allowing precise estimation of volume of the remaining trees, according to the geometric method, in its original or modified form, associated to the estimative equations of the angular coefficients.